2020
DOI: 10.18433/jpps30446
|View full text |Cite
|
Sign up to set email alerts
|

Medicinal Plants as Potential Hemostatic Agents

Abstract: Purpose: Medicinal plants with a variety of phytochemical ingredients remain a potential source for new drug discovery. The use of medicinal herbs in a wide range of diseases and symptoms, such as bleeding, is prevalent in traditional and ethno medicine worldwide. Thus, this work provides a comprehensive review of medicinal plants or their isolated compounds, with respect to their ethno-medicinal use, which have demonstrated the stimulating effect on the hemostasis process. Methods: The relevant studies were w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 67 publications
0
29
0
1
Order By: Relevance
“…In the study of Ebrahimi et al (2020) also were investigated the total of 17 medicinal plants with hemostatic activity. The most frequently studied plant families were Compositae, Lamiaceae, Fabaceae, and Asteraceae.…”
Section: Resultsmentioning
confidence: 99%
“…In the study of Ebrahimi et al (2020) also were investigated the total of 17 medicinal plants with hemostatic activity. The most frequently studied plant families were Compositae, Lamiaceae, Fabaceae, and Asteraceae.…”
Section: Resultsmentioning
confidence: 99%
“…A substantial number of studies have highlighted the role of many polyphenolic compounds in the hemostasis process [18–23] . Besides this, there are a small number of studies related to the impact of lichens and their different extracts on blood coagulation.…”
Section: Discussionmentioning
confidence: 99%
“…There is some evidence for the inhibitory effect of various plant polyphenols or polyphenol‐rich extracts on thrombin and factor Xa. Moreover, some polyphenols can directly inhibit the amidolytic or proteolytic activity of thrombin [21,22] which is a serine protease that catalyzes the conversion of fibrinogen to fibrin in the first steps of the blood coagulation pathway. Therefore, we assume that major bioavailable components of U. decussata ’s AE might directly or indirectly inhibit the active coagulation factors or thrombin in plasma.…”
Section: Discussionmentioning
confidence: 99%
“…Ebrahimi et al comprehensively reviewed the ethno-pharmaceutical applications of medicinal plants or their isolates that stimulate the hemostatic process (62). Although that report included non-Chinese herbal medicine, the authors found via a literature search that several plants could be considered as sources of new herbal hemostatic medicines.…”
Section: Discoveries Of Novel Hemostatic Agents From Chinese Herbal M...mentioning
confidence: 99%